The Impact of a Panenterovirus Vp1 Assay on Our Perception of the Enterovirus Diversity Landscape of a Sample (2016)
The number of independent emergence of recombinant circulating vaccine derived poliovirus serotype 2 (cVDPV2) lineages and the magnitude of the outbreak in Nigeria demonstrates the significance of enterovirus co-infection and its preponderance in the country. Despite this, besides polioviruses, little or no attention is given to enterovirus co-infections. More recently, a reverse-transcriptase semi-nested polymerase chain reaction (RT-snPCR) assay for the direct detection of enteroviruses from clinical specimen was added to the WHO recommended protocols for enterovirus surveillance. We previously showed that primers 292 and 222 (for which AN89 and AN88, respectively, are consensus degenerate hybrid oligonucleotide primers [CODEHOP] versions) mask the presence of enterovirus co-infections. We therefore ask whether the primers AN89 and AN88 used in this recently recommended RT-snPCR protocol, like primers 292 and 222, will also mask the presence of enterovirus co-infections. RNA was extracted from 30 archived samples (both clinical specimen and cell culture isolates) and the VP1 gene amplified using the WHO recommended RT-snPCR assay and modifications that included the primers 187, 188 and 189 for which primer 292 (and consequently AN89) is a consensus. Amplicons were sequenced and isolates identified. Our results showed that primers AN89 and AN88 also mask enterovirus co-infection and inclusion of the primers 187, 188 and 189 allowed the resolution of such mixed isolates. Consequently, expanding the recommended RT-snPCR protocol to include primers 187, 188 and 189 will enable us better detect enterovirus co-infection